(untitled) (Eurasian Research Bulletin, 2023)
The article presents an overview of modern views on the risk factors for malignancy of oral leukoplakia and the latest methods of diagnosis and treatment of this disease. The modern methods of treatment of leukoplakia indicated in this literature review allow us to conclude that when choosing a treatment method, the clinical form of oral leukoplakia should be taken into account, and an integrated approach is the key to effective therapy of this disease